Conceptualising transdisciplinary integration as a multidimensional interactive process. Issue 118 (April 2021) - Pohl, Christian; Klein, Julie Thompson; Hoffmann, Sabine; Mitchell, Cynthia; Fam, Dena
Graphical abstract: Abstract: Integration is a key process in transdisciplinary research and knowledge co-production. Nonetheless, it is often used as a buzzword without specifying what exactly it means or what actually happens during integration. We propose conceptualizing integration as a multidimensional interactive process. We characterize it as an open-ended learning process without pre-determined outcomes. Integration designates relations established throughout a transdisciplinary research process between elements that were not previously related. Those elements are participants in the process and their thought-styles and thought-collectives and more specifically pieces of knowledge, ideas, or practices from different thought-collectives as well as views of individual researchers and practitioners. Integration can happen at manifold instances of a transdisciplinary research process. It can take place among two, several, or all participants and can be one-sided or mutual. It might include insights, practices, frameworks, or concepts shared by two, several, or all participants. Consensus is only one along with other ways of retaining plurality of thought-styles and seeing integration as a balance between them that remains subject to continuous revision. To analyse or achieve effective integration, further dimensions beyond the cognitive have to be taken into account including at least an emotional and a social-interactional dimension.